Environmental Impact of Application on the Concept of Corporate Social Responsibility in Selected EU Countries - Vicianová, Jana Hroncová; Hronec, Štefan (Problemy Ekorozwoju, 2017)
By now, does not suffice to evaluate companies only from an economic point of view, but it is necessary to look at the business and the social and environmental context. Environmental degradation and depletion of natural resources is also reflected in the growth of interest in the area of environmental and social research in the industry. This fact highlights the concept of corporate social responsibility (CSR), according to which the environmental area, the concept of the same weight as economic and social level. The environmental consequences of the company are in advanced economies communicated not only with experts but becomes of interest to the whole society and an integral part of evaluating the success of socio-economic development. The study aims to quantitatively analyse and confirm the existence of a direct and indirect dependence on the number of businesses in individual EU countries to voluntarily implement environmental concepts of social responsibility in the form of environmental management and audit, EMAS. The object of quantitative analysis are selected EU countries.